Mengimplementasikan Etika dan Kepemimpinan: Pendekatan Perilaku dalam Konteks Organisasi - Harin Aulia Sajidah; Eva Ayu Lestari; Dhanang Cahya Prabawa; Mohammad Isa Anshori (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Leadership is an important factor that determines the success of an organization in achieving its goals. A leader needs to keep his behavior and ethics in conducting his leadership. By applying good behavior and ethics it can have a positive influence on the performance of employees in achieving the goals of the organization. The aim of this research is to understand that the implementation of ethics and leadership with behavioral approaches is highly influential to the organization. Through this qualitative research, it is expected that research can provide in-depth insight into ethics and leadership with behavioral approaches to organizations.